The influence of warming and biotic interactions on the potential for range expansion of native and nonnative species. Issue 5 (18th August 2020) - von Holle, Betsy; Weber, Sören E; Nickerson, David M
Abstract: Plant species ranges are expected to shift in response to climate change, however, it is unclear how species interactions will affect range shifts. Because of the potential for enemy release of invasive nonnative plant species from species-specific soil pathogens, invasive plants may be able to shift ranges more readily than native plant species. Additionally, changing climatic conditions may alter soil microbial functioning, affecting plant–microbe interactions. We evaluated the effects of site, plant–soil microbe interactions, altered climate, and their interactions on the growth and germination of three congeneric shrub species, two native to southern and central Florida ( Eugenia foetida and E. axillaris ), and one nonnative invasive from south America ( E. uniflora ). We measured germination and biomass for these plant species in growth chambers grown under live and sterile soils from two sites within their current range, and one site in their expected range, simulating current (2010) and predicted future (2050) spring growing season temperatures in the new range. Soil microbes (microscopic bacteria, fungi, viruses and other organisms) had a net negative effect on the invasive plant, E. uniflora, across all sites and temperature treatments. This negative response to soil microbes suggests that E. uniflora 's invasive success and potential for range expansion are due to other contributing factors, e.g. higher germination and growth relative to native Eugenia . The effect of soil microbes on the native species depended on the geographic provenance of the microbes, and this may influence range expansion of these native species. Abstract : Species ranges are expected to shift in response to climate change; however, it is unclear how species interactions will affect range shifts. Our study demonstrates that, in the predicted future range, plant–soil microbial interactions appeared as a form of biotic resistance to one native and one nonnative shrub species, however soil microbes facilitated a native species in the future range, under warmer temperatures. Plant–soil microbe interactions for the native congeners depended on the geographic provenance of the soils, which may affect their ability to expand their ranges.